The definitive collection [compact disc] - Richie, Lionel (Motown Records, 2003)
From his time in the Commodores to his solo career, Lionel Richie has been one of music most successful singers and songwriters. This definite collection features his greatest hits, including seven of his number one songs including Hello and Truly.